The politically incorrect guide to capitalism - Murphy, Robert P. (Robert Patrick), 1976- (Washington, DC : Regnery Pub. ; Lanham, MD : Distributed to the trade by National Book Network, 2007)
An irreverent look at capitalism that exposes common fallacies and offers simple explanations of complex issues related to capitalism and its role in the world's economy.
ch. 14. Trade wars -- Tariffs are taxes on Americans -- Protecting jobs? -- Classical wisdom -- Debunking the deficit -- The trade deficit : follow the money -- ch. 15. Making money in the global village -- Manufacturing a crisis -- Outsourcing destroys jobs? -- Outsourcing makes America richer -- The high-tech sector : another phony crisis -- Capital export is a capital idea -- We're from the world government and we're here to help -- ch. 16. The investor class : in other words, you and me -- Interest : sooner is better than later -- The importance of middlemen -- The farsighted speculator -- Futures and other derivatives : to each according to his ability -- Raiders of the lost corporation -- A twelve-step plan for understanding the free market -- Acknowledgments -- Notes -- Index.
Includes bibliographical references (pages 189-194) and index.
Keywords: Capitalism -- United States; Free enterprise; Economic history; Economic policy